Idiopathic enlargement of the right atrium: 23 year follow up of a familial cluster and their unaffected relatives. Issue 11 (14th October 2004) - Kurz, D J; Oechslin, E N; Kobza, R; Jenni, R
Abstract : Objective: To evaluate the long term outcome of familial idiopathic enlargement of the right atrium (IERA) and the risk of developing this disorder among unaffected offspring. Design: 23 year follow up study. Patients: 14 members (eight men, mean age 54 years, range 40–78) of a pedigree with familial IERA. Methods: All patients were examined clinically and echocardiographically in 1979 and 2002. Normal cross sectional dimensions of the right atrium were derived from echocardiographic evaluation of 100 people (47% men) with no structural or haemodynamic signs of heart disease. The 90th centile was chosen as the upper normal limit. IERA was defined as an increased right atrial long axis indexed to body surface area (RALAXi, men > 2.6 cm/m 2, women > 2.8 cm/m 2 ) in the absence of other cardiac abnormalities. Severe IERA was defined arbitrarily as RALAXi ⩾ 4 cm/m 2 . Results: The course of the two index patients with severe IERA diagnosed in 1979 was complicated by atrial fibrillation, systemic embolism, and symptoms of heart failure without systolic dysfunction, resulting in the death of one man (77 years old). One of two patients with initially mild forms progressed to severe IERA. All of the initially unaffected offspring (n = 9) remained asymptomatic, although four of them had developed mild IERA. Conclusions: During 23 years' follow up, severe IERA induced atrial fibrillation, systemic embolism, and symptoms of heart failure without systolic dysfunction in all cases in this family. Mild IERA seems to become manifest during middle age and may be followed by gradual progression to clinically relevant disease.